ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN WHOLESALE AND RETAIL TRADE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Febri Kristianingsih, 11.05.52.0095; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2015)
The study intends to determine the â analysis of the factors that influence the capital structure in Wholesale and retail Trade companies that listed on the stock exchange Indonesiaâ. The population is all Wholesale and Retail Trade company in tock Exchange Indonesia Swith a sample of 33 companies and research over the period 2010 to 2013. This samples were taken inthis study is a total of 18 companies.the sampling techniques is used purposive sampling. The analyzer that is used in this research is multiple regression analysis. The results showed that the coefficient of determintion in this study is the adjusted R-square values of 27,3%. While for test F-test shows that, between current ratio (CR), the level of sales (TP), Company size (Size), business risk (ROE) togather effect the capital structure (DER). And partial hypotesis testing results show that there is positif effect of current ratio, the level of sales and business risk to capital structure. While for the size of the company negatively affect the capital structure.Keywords: Current Ratio, The level of Sales, Company Size, Return On Equity, Capital Structure